1993
DOI: 10.1083/jcb.123.4.799
|View full text |Cite
|
Sign up to set email alerts
|

GTP hydrolysis by complexes of the signal recognition particle and the signal recognition particle receptor.

Abstract: Abstract. Translocation of proteins across the endoplasmic reticulum membrane is a GTP-dependent process. The signal recognition particle (SRP) and the SRP receptor both contain subunits with GTP binding domains. One GTP-dependent reaction during protein translocation is the SRP receptor-mediated dissociation of SRP from the signal sequence of a nascent polypeptide. Here, we have assayed the SRP and the SRP receptor for GTP binding and hydrolysis activities. GTP hydrolysis by SRP was not detected, so the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
52
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 48 publications
6
52
1
Order By: Relevance
“…At the onset of co-translational protein translocation in Eukarya, ribosomes in the process of synthesizing signal peptide-bearing nascent polypeptides are recognized by SRP and delivered to the ER membrane via the affinities of SRP for its receptor 12,13 and of the ribosome for the Sec61 complex. 14,15 Similarly, bacterial ribosomes have been shown to specifically bind to SecYEG complexes, 20,21 although the physiological significance of this finding remains the subject of investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the onset of co-translational protein translocation in Eukarya, ribosomes in the process of synthesizing signal peptide-bearing nascent polypeptides are recognized by SRP and delivered to the ER membrane via the affinities of SRP for its receptor 12,13 and of the ribosome for the Sec61 complex. 14,15 Similarly, bacterial ribosomes have been shown to specifically bind to SecYEG complexes, 20,21 although the physiological significance of this finding remains the subject of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…10 SRP binding subsequently slows or prevents the continuation of further protein synthesis. 11 The ternary complex of ribosome -nascent polypeptide chain -SRP then interacts with the ER membrane via the affinities of SRP for the membrane-associated SRP receptor, 12,13 but also via the interaction between the ribosome and Sec61abg, the core of the translocation complex (the "translocon"). 14,15 Once delivered to the translocon, the arrest of protein synthesis mediated by SRP is removed and synthesis of the nascent chain into the translocon, and hence, across the ER membrane, proceeds.…”
Section: Introductionmentioning
confidence: 99%
“…Using an in vitro membrane repopulation assay, it has been shown that site-specific mutations in the GTPase consensus motifs of mammalian SRa disrupt its function (71). Although photoaffinity labeling in vitro demonstrates that Srp54 and both subunits of the SRP receptor are GTP-binding proteins (20), GTP hydrolysis by mammalian Srp54 could be detected only in the presence of the SRP receptor and SRP RNA (21,53,54,66). In contrast, the M. mycoides Srp54 protein displays readily detectable GTPase activity in the absence of other factors (81).…”
mentioning
confidence: 99%
“…At the membrane, the SRP⅐SR complex unloads its cargo to the SecYEG or Sec61p translocase, which mediates the integration or translocation of the nascent protein across the membrane (9,10). In addition, GTP hydrolysis is activated in the SRP⅐SR complex to drive their disassembly, allowing SRP and SR to enter the next round of targeting (11)(12)(13).…”
mentioning
confidence: 99%